Self-perceived competencies in the diagnosis and treatment of mental health disorders among general practitioners in Lima, Peru - Zafra-Tanaka, Jessica Hanae (2018)
Aim: To assess the self-perceived competencies in diagnosing and treating patients with mental health disorders, among recently graduated general practitioners (GPs) from Lima, Peru. Methods: A cross-sectional study was performed in April 2017 at a General Practitioner’s meeting held for those who were going to perform the social service, by the Peruvian College of Physicians in Lima. Attendees were invited to answer a questionnaire that evaluated their self-perception of competence in diagnosing and treating four different mental health disorders; major depression, anxiety disorder, alcohol dependence, and schizophrenia. Results: Out of 434 evaluated GPs, the following percentages were self-perceived as competent in their adequate diagnosis of depression (70.5%), anxiety (73.3%), alcohol dependence (67.6%), and schizophrenia (62.0%). Concerning pharmacological treatment, these percentages were 46.6, 47.5, 39.0 and 37.6%, respectively. Referring to all the studied mental disorders, 41.6% of participants self-perceived competence in providing an adequate diagnosis, 36.1% in providing non-pharmacological treatment, and 20.1% in providing pharmacological treatment. Conclusion: The rate of adequate self-perceived competences was higher for diagnosis than for treatment of patients with mental health disorders. These results highlight the importance of designing and implementing interventions to improve medical education so as to develop the skills necessary to confront mental health disorders.